Dinamika Sosial dalam Novel Pencari Harta Karun Karya Agnes Jessica dan Novel Five On A Hike Together Karya Enid Blyton - Huda, Miftakhul; Niasih, Anggi; Purwanti, Riska Dewi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
This study aims to describe the elements of the social layers, the forms of social changes, the factors that influence social changes, and the process of social changes in the novels entitled Pencari Harta Karun and Five on a Hike Together. This study uses a qualitative approach with comparative literary research approach. The data of this study are words and sentences in the novels Pencari Harta Karunand Five on a Hike Together which show the process of social dynamics. The research data were analyzed using intertextuality technique. The results of this study are as follows. First, concerning the elements of social layers. Second, the forms of social changes. Third, the factors that influence social change. Fourth, the process of social changes.